The effectiveness of Bisinglah, BEB! A classroom-based hearing conservation programme for youth - Ismail, Noraidah; Ishak, Kamarul Akmal; Rahmat, Sarah; Zakaria, Mohd Normani (Nova Science Publishers, 2022)
Similar to other developing countries, youths in Malaysia are at risk of suffering from noise-induced hearing loss (NIHL) due to extreme leisure noise exposure. To minimize the incident of NIHL among youth, a Malay classroom-based hearing intervention programme known as Bisinglah, BEB! (in English: HEY! It’s Loud!) has been developed. The programme consists of five modules; i) Sound energy, ii) Anatomy and hearing mechanism, iii) Hearing loss, iv) Dangerous sound, and v) How to protect our ears. As such, the aim of the present study was to evaluate the effectiveness of the Bisinglah, BEB! programme in increasing youth’s knowledge and promoting a healthy hearing attitude towards noise. Eighty participants were assigned into two groups (intervention and control). All participants completed a set of questionnaires (Youth Attitude Towards Noise Scale-Malay, YANS-M and quiz) to measure their attitude and knowledge at baseline, 1-month and 3-month post-intervention sessions. Only participants in the intervention group filled in the post-immediate questionnaire after completing the intervention. It was found that gender did play a significant role in describing the participants’ attitude and knowledge towards the noise. The post-immediate measurement score for the intervention group exhibited a significant improvement compared to the baseline (p < 0.05). These improvements were maintained for at least three months after undergoing the programme. To conclude, the Bisinglah, BEB! programme was reasonably effective in encouraging healthy hearing attitudes and knowledge towards noise. However, further research is warranted to investigate the long-term effects of this programme involving larger youth samples in Malaysia.